Examining Determinants of Self-representation on Facebook: A Study of Pakistani Youth - Sabah Arshad Abbasi; Bakht Rawan; Muhammad Sher Ali Joni, (ASIAN Journal of International Peace & Security (AJIPS), 2021)
The last two decades are characterized by a continuous increase in the use of social networking sites (SNS) amongst people of all age groups across the globe. Users belonging to different demographic groups have different motives/needs which make them use these SNS. Furthermore, every individual has different ways of self-representation on these social networking sites, which are related to certain motives and needs that determine the way they represent themselves on SNS in a particular way. Hence, the present research was designed to know the determinants/ motives of self-representation on Facebook by Pakistani youth. It investigated four different sociopsychological determinants (motives) of self-representation of Facebook users. These dimensions were (i) social and affection motive, (ii) recognition motive, (iii) exhibitionism motive and (iv) cognitive motive. The study also examined the effects of gender and age differences on the selfrepresentation motives of Facebook users. The researchers used survey technique. Data were collected from students of International Islamic University, Islamabad through questionnaire by employing convenient sampling techniques. Analysis of the collected data shows that Facebook users’ main motives behind self-representation were social and affection, and exhibitionism. Results also demonstrated that these motives were not the same for males and females as well as users of different age groups.